2012
DOI: 10.1097/bot.0b013e318238b3a2
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Effect of Prosthetic Design on Radiocapitellar Stability in a Terrible Triad Model

Abstract: Objectives: The integrity of elbow soft tissues affects radiocapitellar joint stability in the presence of bipolar radial head (RH) prostheses. This study examined the effect on radiocapitellar stability of monopolar designs versus bipolar RH prostheses in an elbow model with a surgically controlled terrible triad injury.Methods: In each of 8 fresh-frozen elbow specimens (4 male and 4 female), a terrible triad fracture dislocation was created through soft tissue releases, coronoid fracture, and RH resection. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…Several radial head prosthesis (RHP) designs are currently available. Bipolar implants allow for more movement of the cup with respect to the capitellum, despite suboptimal reproduction of anatomic and biomechanical properties [14,28,29]. However, studies analyzing implant characteristics have demonstrated no significant difference in clinical outcomes and report high satisfaction for various designs at both short-and long-term post-operative follow-up [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several radial head prosthesis (RHP) designs are currently available. Bipolar implants allow for more movement of the cup with respect to the capitellum, despite suboptimal reproduction of anatomic and biomechanical properties [14,28,29]. However, studies analyzing implant characteristics have demonstrated no significant difference in clinical outcomes and report high satisfaction for various designs at both short-and long-term post-operative follow-up [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated posterolateral dislocations increase the risk of hypermobility of the cup secondary to radiocapitellar instability and may lead to complete dissociation of the cup from the stem [15,26]. Monopolar prostheses are the implants of choice in cases with associated ligamentous injury because they allow for superior radiocapitellar stability thanks to increased concave compression of the implants [28,29]. Tissue integrity did not affect implant choice for each patient as only one design was available at the time of surgery for all patients in this series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 It should be noted that monopolar implants can better resist radiocapitellar subluxation in the setting of soft-tissue deficient cadaver elbows, 32 particularly in a terrible triad model.…”
Section: Bipolar Prosthesismentioning
confidence: 99%
“…Conversely, both Schneeberger et al [16] and Pomianowski et al [14] demonstrated significant improvements in ulnohumeral laxity with a monopolar implant compared with a bipolar implant in terrible triad models. The biopolar implant has been demonstrated to provide less stability in an elbow with no ligamentous structures [4,11]. The specific dependence and influence of the lateral collateral ligament has been shown to be more critical with a bipolar implant design [5].…”
Section: Introductionmentioning
confidence: 99%